2021
DOI: 10.1039/d1ay00075f
|View full text |Cite
|
Sign up to set email alerts
|

Quick determination and discrimination of commercial hand sanitisers using attenuated total reflectance-Fourier transform infrared spectroscopy and chemometrics

Abstract: Due to the outbreak of COVID-19 pandemic, practicing personal hygiene such as frequent hand sanitising becomes a norm. The making of effective hand sanitiser products should follow the recommended formulations,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…But, it is clearly indicated that such addition of fragrances and colorants is not recommended due to the potential risk of allergic reactions and might increase the risk of ingestion by children [ 13 , 33 , 34 ]. In addition to this, the antimicrobial effectiveness of the products may be compromised by these agents which otherwise their influence should be justified with tests [ 13 , 17 ]. It is also possible that the inclusion of additional ingredients, particularly when untested, would affect product efficacy, stability, and safety [ 4 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But, it is clearly indicated that such addition of fragrances and colorants is not recommended due to the potential risk of allergic reactions and might increase the risk of ingestion by children [ 13 , 33 , 34 ]. In addition to this, the antimicrobial effectiveness of the products may be compromised by these agents which otherwise their influence should be justified with tests [ 13 , 17 ]. It is also possible that the inclusion of additional ingredients, particularly when untested, would affect product efficacy, stability, and safety [ 4 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increasing consumer demand, these products could become easy targets of fraud or counterfeiting by bulking the preparation by diluting the alcohol content with water or cheaper substitutes like methanol which end up with a less functional product [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…determination and discrimination of commercially available hand sanitizers using ATR-FTIR spectroscopy. 189 During the COVID-19 pandemic, the demand for hand sanitizer products increased, making it a prime candidate for counterfeiting and the selling of unsafe products. This work investigated the spectra of 50 samples using LDA to classify the products into eight distinct groups.…”
Section: T H Imentioning
confidence: 99%
“…They also noted the change in the solvent peak over time, dominating the spectra initially, tracking its disappearance during drying, and identifying the absence of the band when completely dried. Teoh et al created a method for the determination and discrimination of commercially available hand sanitizers using ATR-FTIR spectroscopy . During the COVID-19 pandemic, the demand for hand sanitizer products increased, making it a prime candidate for counterfeiting and the selling of unsafe products.…”
Section: Chemistry: Trace Evidencementioning
confidence: 99%